Work to Family Enrichment and Job Enrichment Integration: A Systematic Literature Review Approach from a Philosophical Perspective - Marsya Aulia Rizkita; Kukuh Judy Handojo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This paper systematically reviews the drivers of work-family enrichment and job enrichment within the 2019–2024 timeframe from a philosophical perspective. The study employs a Systematic Literature Review (SLR) approach, utilizing Publish or Perish and the Scopus database to identify and evaluate relevant papers. The article's key conclusions indicate that the ontological review conceptualizes work-family balance as a complex interplay between enrichment and conflict, which can significantly impact each employee's well-being. The epistemology review focuses on the study's use of a theoretical framework and methodology. The axiology examines how these two concepts enhance employee psychology, work engagement, and career achievement, as well as their positive impact on job satisfaction. The findings of the philosophical analysis, which may be influenced by specific viewpoints, highlight the research gap. To improve the well-being of both the organization and its employees, this article provides recommendations for future research and organizational practices.